Markets against Modernity Ecological Irrationality, Public and Private. - Murphy, Ryan H. (Capitalist thought: studies in philosophy, politics, and economics., 2019)
Economist Ryan Murphy explains divergences between popular and informed opinion on the value of the institutions of the modern world, including globalized markets, science, and pluralism. The public expresses hostility for these institutions both in the voting booth and in their private lives, and even through the marketplace itself.